Nye perspektiv på Hans Nielsen Hauge - Farstad, Eli Morken (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Hans Nielsen Hauge established and led at the end of the 18th century Norway's first nationwide popular movement, a low church network that would leave its mark on everyday life, business development and politics in the transition from absolute monarchy to representational government. People called themselves Haugians long after Hauge's death in 1824. It was a spiritual awakening on a scale that deserves considerable room when we write the history of modern Norway. This book provides a new perspective on the roots of the Hauge movement in the religious mentality of the 18th century, on how it functioned in its most radical phase up to 1814, and on the importance of the network for economic modernization and political mobilization in the subsequent decades. Retrospective interpretations of Hauge's complex endeavor are also explored. In sum, the nine chapters provide a broader understanding of the Hauge movement and the era in which it flourished. We hope that the book also sheds light on the state of Norway's people, government and religiosity today, over 250 years after Hauge's birth. The book has been edited by research fellow Eli Morken Farstad and associate professor Kristian Holen Nymark, both historians at the University of South-Eastern Norway.